Creative Catholic Religious Education Learning: Integrating Creativity Education and Growth Mindset to Support SDG 4 in Senior High Schools - Alfonsus Mudi Aran (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
This study explores the integration of Creativity Education and Growth Mindset in Catholic Religious Education (CRE) at Senior High Schools and examines its alignment with the Sustainable Development Goal (SDG) 4, focusing on quality and inclusive education. Using a Systematic Literature Review based on the PRISMA 2020 protocol, the study analyzed 1,263 articles from scientific databases, narrowing down to 106 relevant studies. The findings highlight that Creativity Education fosters critical thinking, cognitive flexibility, problem-solving, and the integration of moral and spiritual values. Growth Mindset enhances students’ intrinsic motivation, perseverance, and resilience, creating an adaptive, innovative, and inclusive learning environment. The synthesis led to the development of an integrative learning model, which includes the Creative Reflective Learning Cycle, Faith-Based Project Learning, Creative Growth Dialogue, and Digital Creativity Integration. This model aims to holistically develop students’ cognitive, creative, moral, and spiritual capacities. The study demonstrates that the combination of Creativity Education and Growth Mindset enriches CRE pedagogical practices and supports the development of 21st-century skills, such as critical thinking, collaboration, digital literacy, and moral literacy. It concludes that project-based learning, digital technology integration, and curriculum adjustments are vital steps in improving learning quality and inclusiveness. The study recommends further empirical research to test the effectiveness of the proposed model.